2010
DOI: 10.4039/n09-060
|View full text |Cite
|
Sign up to set email alerts
|

Spring emergence of CanadianDelia radicumand synchronization with its natural enemy,Aleochara bilineata

Abstract: Abstract-To characterize time of spring emergence following post-diapause development, Delia radicum (L.) (Diptera: Anthomyiidae) from Saskatchewan, Manitoba, and southwestern Ontario were collected in fall, maintained over winter at 1 uC, then transferred to higher constant temperatures until adult emergence. At each location there were ''early'' and ''late'' phenotypes. Truncated normal models of temperature dependency of development rate were fitted for each phenotype from each location. We provide the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…2005). Richness and diversity may have been underestimated in 2010 fall hedgerows, as an asymptote was not reached. However, this is of minor importance, as the 2010 fall hedgerow assemblage was shown to be more species rich and diverse than that of soybean in the same year, despite this bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2005). Richness and diversity may have been underestimated in 2010 fall hedgerows, as an asymptote was not reached. However, this is of minor importance, as the 2010 fall hedgerow assemblage was shown to be more species rich and diverse than that of soybean in the same year, despite this bias.…”
Section: Discussionmentioning
confidence: 99%
“…Rove beetles (Coleoptera: Staphylinidae) are recognised as important components of agroecosystems worldwide and are mostly known for their mitigation of agricultural yield loss by predation of diverse pest arthropods, such as spider mites in Japan (Kishimoto and Adachi 2008), cereal aphids in central Europe (Dennis and Wratten 1991), horn flies in Florida (Hu and Frank 1995), and cabbage maggots in central Canada (Andreassen et al 2010). Most of our knowledge about staphylinids in agroecosystems is based on research in Europe (e.g., Clough et al 2007;Balog et al 2008), where the rove beetle assemblages are comprised mostly of generalist predators.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary analysis suggested that some pupal development had occurred prior to the start of the 2011 and 2012 pupal development experiments. To allow results from both experiments to contribute to parameter estimates, Taylor's () equation was inverted, to produce a reciprocal model predicting days to emergence (Andreassen et al., ), and the term D p was introduced: Days=1Rme12normalTTmnormalTnormalσ2normalDnormalp×Experiment_Codewhere Experiment_Code was 0 for the 2011 experiment and 1 for the 2012 experiment. As pupae were randomly allocated to temperature treatments in each experiment, D p is an estimate of the average difference in days between experiments in the amount of prior pupal development.…”
Section: Methodsmentioning
confidence: 99%
“…For example, models using heat units improve pest management decisions for codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae), by providing information about its seasonal dynamics that impact timing insecticide applications (Barnett et al 1991, Knight 2007). Other tactics, such as biological control, are similarly dependent on pest phenology since natural enemies often target-specific life stages (Mills 1992) and need to synchronize with the pest for long-term control (Stiling 1993, Andreassen et al 2010). Ferrisia gilli 's phenology is described in Haviland et al (2012): nymphs of the overwintered F. gilli population migrate from their protected locations in the cracks and crevices of the tree trunk, to scaffolds and smaller tree branches in April and May as the tree begins to leaf out.…”
Section: Introductionmentioning
confidence: 99%